Mucosal immunodeficiency in smokers, and in patients with epithelial head and neck tumours. Issue 4 (April 1990) - Barton, J R; Riad, M A; Gaze, M N; Maran, A G; Ferguson, A
Abstract : Cigarette smoking influences the risk of orogastrointestinal disease in both protective (ulcerative colitis), and inductive (squamous tumours of the head, neck and oesophagus) roles. In order to study the effects of smoking on mucosal immunity, salivary immunoglobulins were measured in pure parotid saliva from groups of healthy non-smokers, smokers, and exsmokers and from patients with epithelial head and neck tumours, both untreated and after radiotherapy. Of the healthy individuals, smokers had significantly lower salivary IgA and higher IgM concentrations than did non-smokers. The effect on IgA was dose related, and reversible after cessation of smoking. Likewise, in patients with head and neck tumours (the majority being smokers), salivary IgA concentration was reduced and IgM increased when compared with non-smoking controls. Results were similar before and after radiotherapy. This study provides evidence of the effects of smoking on mucosal immunity as evaluated by parotid salivary immunoglobulins. Further studies of the influence of smoking on secretory immunity are indicated.